HARDINESS ON WOMEN POST DIVORCE - Reza Fahmi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The reason of this consider was to decide the portrayal of toughness in post-divorce ladies and to discover out what components impact solidness in post-divorce ladies in Nagari Sungai Nanam, Solok Rule. This ponder employments a subjective investigate strategy with a case consider approach. The testing method in this inquire about is purposive testing method. The subjects in this ponder were three individuals. Information collection procedures in this ponder were perception, interviews, and documentation. Information investigation procedures utilizing topical investigation strategies (topical examination). The comes about of this consider were gotten from information on subjects B, MA and SY who have solidness in themselves which is shaped due to commitment, control and challenges in carrying out their lives.